Overview of the Accuracy of Inpatient Dyspepsia Diagnosis Codes Based on ICD-10 at Hospital X Bengkulu City: Gambaran Keakuratan Kode Diagnosis Dyspepsia Rawat Inap Berdasarkan ICD-10 di Rumah Sakit X Kota Bengkulu - Putri, Liza; Agusianita, Agusianita; Khairunnisa, Alfi (Procedia of Engineering and Life Science, 2025)
Problem of Coding activities for disease diagnosis are very important during medical record services in hospital installations. To get the correct coding, the activities carried out look at the medical resume, admission and discharge summary and supporting sheet where the coding is carried out by the medical record staff, who is responsible for the accuracy of the Dyspepsia code. If coding is not carried out accurately, it will result in errors in disease recording indexes and procedures, inaccurate report information data and inaccurate INA-CBG rates. Objective for Known description of the accuracy of inpatient dysspecia diagnosis codes based on ICD-10 at Rafflesia Hospital, Bengkulu City. Method:This type of research is descriptive observational through direct observation of the population and a sample of 57 medical record files with a diagnosis of dyspepsia cases. The data used in this research is secondary data which was processed univariately. Results of the 57, the majority, namely 36(63,1%) of the dyspepsia diagnosis codes in the medical record files were accurate and 21 (36,9%) of the dyspepsia diagnosis codes in the medical record files were inaccurate. The completeness of the recording files was 36 files (63,1%), the completeness of the incomplete recording files was 31 files (36.9%). Suggestion: Coders should refer to ICD-10 in assigning codes and attend training to deepen their understanding of the implementation of classification and codification.